Thermally-electrically tunable graphene-based guided-mode resonant perfect absorber - Huang, Ze-Tao; Jiang, Hao-Yi; Wang, Zi-Ye; Qing, Ye-Ming; Li, Bing-Xiang (IEEE photonics technology letters, 2023)
We propose a thermally-electrically tunable perfect absorber based on graphene and amorphous silicon. Numerical results reveal that a perfect absorption with narrow bandwidth can be induced owing to critical coupling with guided-mode resonance. The thermal tuning of resonant wavelength is realized via the electrically controlled Joule heating with a high tuning efficiency and linear controllability due to the linear relationship between the refractive index of amorphous silicon and the variation of temperature. Moreover, by adjusting the applied gate voltage, the chemical potential of graphene can be electrically modified and lead to a change of optical absorption, henceforth implementing a rapid switching of perfect-absorption and perfect-reflection. It is remarkable that the proposed absorber features a simple structure, perfect absorption, and efficient thermal-electric tunability, manifesting tremendous potential applications in modulator, optical switching, selective filter, etc.